2015
DOI: 10.1007/s00402-015-2163-4
|View full text |Cite
|
Sign up to set email alerts
|

Thumb fingertip reconstruction with palmar V–Y flaps combined with bone and nail bed grafts following amputation

Abstract: We believe that the combination of palmar V-Y flap and bone and nail bed grafts provides a distinct advantage over other choices. It improves function when replantation is not an option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…7,8 Reconstruction of the thumb tip injury has various options. 6,9,10 Whenever possible and feasible, reimplantation of the amputated part is the option for reconstruction. Other options include free pulp transfer, free toe transfer, neurovascular islanded pedicled flap, Moberg's flap, Brunelli's flap, cross-finger flap, etc.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Reconstruction of the thumb tip injury has various options. 6,9,10 Whenever possible and feasible, reimplantation of the amputated part is the option for reconstruction. Other options include free pulp transfer, free toe transfer, neurovascular islanded pedicled flap, Moberg's flap, Brunelli's flap, cross-finger flap, etc.…”
Section: Discussionmentioning
confidence: 99%
“…However, shortening of the postoperative finger length happens more frequently with DAF than with replantation. Zhou et al 16 reported that fingertip replantation of the thumb using a palmar V-Y advancement flap with a nail bed and bone graft achieved more than 70% length in 78.6% of patients. Hwang et al 3 showed that simultaneous DAF and nail bed graft resulted in 80% of fingertip amputations retaining at least 70% of the length of the uninjured finger.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additionally, thumb fingertip injury is among the most common injuries in the upper limb. 10 The fingertips are also the most important organs for tactile sensation. Therefore, reconstruction of sensation of the thumb fingertip is considered essential by hand surgeons after a thumb fingertip injury.…”
Section: Discussionmentioning
confidence: 99%